2015
DOI: 10.1007/s11060-015-1979-7
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric brain tumors in a low/middle income country: does it differ from that in developed world?

Abstract: Central nervous system (CNS) tumors are the most frequent solid tumors in children and adolescents. The epidemiology of these tumors differs in areas of the world. However, very little data is available in the low/middle income countries (LMIC). The aim of this study is to describe the characteristics of primary childhood brain tumors treated at a leading LMIC pediatric cancer hospital and its difference from that in other countries. One thousand one hundred fourteen children and adolescent having CNS tumors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
2
36
1
Order By: Relevance
“…Several series' report a male predominance in all parts of the CNS [9,11,18,19]. In our series, PCF tumours were slightly more prevalent in males.…”
Section: Discussionsupporting
confidence: 54%
“…Several series' report a male predominance in all parts of the CNS [9,11,18,19]. In our series, PCF tumours were slightly more prevalent in males.…”
Section: Discussionsupporting
confidence: 54%
“…Data collected by the Pan American Health Organization (PAHO) demonstrates that Peru is an example of how advances in health care have decreased mortality due to communicable disease or other preventable diseases while mortality due to malignancy remains relatively unchanged (www.PAHO.org ; Supplemental Figure 1 ). While the survival rates for average risk medulloblastoma are approaching 80-90% in HIC, survival rates in our study, as well as those in other LMIC suggest areas that can be addressed that will allow for improvement in survival rates in pediatric medulloblastoma in Peru 7,8,10,21 . Univariate analysis demonstrated that histologic sub-type, presence of metastasis at diagnosis, and treatment post-2008 all negatively affected outcomes in our study (Table 4 ).…”
Section: Discussionmentioning
confidence: 55%
“…[6] A 10-microRNA (miRNA) expression signature profiling data of 222 GBM patients were tested, seven of which were risky and three protective RNAs. [7] Patients were divided into different groups based on the high-or low-risk scores which differed significantly in terms of both short-and long-term survival. Similarly, 14 genes GBM prognostic signature used weighted gene score can be used as an independent predictor of survival as shown in 123 patients.…”
Section: Impact Of Pathology and Molecular Biology On Clinical Outcommentioning
confidence: 99%
“…There have been studies to test the suggestions that there are differences in epidemiological variables, clinical presentation, prognostic factors, and occasional behavior to therapy, when western patients are compared to their Indian counterparts. [5][6][7] As an example, western investigators have documented the presence of the JC viral (JCV) genome in a variety of brain tumors, particularly in medulloblastomas, gliomas, and ependymomas. However, in a study of 22 medulloblastoma patients, JCV antigens could not be detected by immunohistochemistry in the tumor tissues of Indian children with medulloblastomas.…”
mentioning
confidence: 99%